The influence of tectonics, sea‐level changes and dispersal on migration and diversification of Isonandreae (Sapotaceae). (3rd December 2013) - Richardson, James E.; Bakar, Azrul M.; Tosh, James; Armstrong, Kate; Smedmark, Jenny; Anderberg, Arne A.; Slik, Ferry; Wilkie, Peter
<x xml:space="preserve">Abstract</x> Internal transcribed spacer (ITS) ribosomal DNA sequence data were generated for 80 of the c. 200 species of Isonandreae and were added to data from African and Neotropical representatives in subfamily Sapotoideae and outgroups in Sapotaceae. Bayesian dating and ancestral area reconstruction indicated that Isonandreae are derived from within an African grade. Multiple Australasian species or lineages are derived from Sundanian lineages in South‐East Asia with stem ages originating from the late Oligocene. Sri Lankan and Indian lineages are also derived from Sundanian lineages. Our results are consistent with migration from Africa into Sundania followed by numerous over‐water dispersal events across Wallace's Line into Australasia and migration from Sundania to the Indian subcontinent. Pleistocene speciation indicates that sea‐level changes during that epoch could have been responsible for some species diversification in Sundania. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 174, 130–140.